ADAMTS19‐associated heart valve defects: Novel genetic variants consolidating a recognizable cardiac phenotype. Issue 1 (19th May 2020) - Massadeh, Salam; Alhashem, Amal; van de Laar, Ingrid M.B.H.; Alhabshan, Fahad; Ordonez, Natalia; Alawbathani, Salem; Khan, Suliman; Kabbani, Mohamed S.; Chaikhouni, Farah; Sheereen, Atia; Almohammed, Iman; Alghamdi, Bader; et al.
Abstract: Recently, ADAMTS19 was identified as a novel causative gene for autosomal recessive heart valve disease (HVD), affecting mainly the aortic and pulmonary valves. Exome sequencing and data repository (CentoMD) analyses were performed to identify patients with ADAMTS19 variants (two families). A third family was recognized based on cardiac phenotypic similarities and SNP array homozygosity. Three novel loss of function (LoF) variants were identified in six patients from three families. Clinically, all patients presented anomalies of the aortic/pulmonary valves, which included thickening of valve leaflets, stenosis and insufficiency. Three patients had (recurrent) subaortic membrane, suggesting that ADAMTS19 is the first gene identified related to discrete subaortic stenosis. One case presented a bi‐commissural pulmonary valve. All patients displayed some degree of atrioventricular valve insufficiency. Other cardiac anomalies included atrial/ventricular septal defects, persistent ductus arteriosus, and mild dilated ascending aorta. Our findings confirm that biallelic LoF variants in ADAMTS19 are causative of a specific and recognizable cardiac phenotype. We recommend considering ADAMTS19 genetic testing in all patients with multiple semilunar valve abnormalities, particularly in the presence of subaortic membrane. ADAMTS19 screening in patients with semilunar valve abnormalities is needed to estimate the frequency of the HVD related phenotype, which might be not so rare. Abstract :